Capacity worth of energy storage systems in renewable power generation plants - Li, Jinbin. (2010)
With the advance in renewable generation technologies, the cost of renewable energy becomes increasingly competitive when compared to other fossil fuel-based generation resources. It is economically beneficial to integrate large amounts of renewable capacity in power systems. Unlike other traditional generation facilities, however, using renewable resources for generation presents technical challenges in producing continuous and controllable electric power. In this report, an Energy Storage System (ESS) is integrated to smooth the variations in renewable power production and ensure the output power more controllable. Since it requires capital investment for the storage devices, it is important to obtain reasonable estimate of the storage capacities to achieve the desired applications. This project study is therefore formulated as an optimization problem in determining the power and energy capacities of the ESS. The objective is to make the renewable power more reliable and simultaneously maximize the economic benefits that can be obtained from the scheme. To make the results more convincing, analyses in this report starts with wind generation, for wind has greater variability and unpredictability than other renewable sources. A battery energy storage system (BESS) is considered in the scheme. However, the methods presented here are suitable for any type of energy storage methods and are also useful for intermittent renewable energy resources other than wind.